2020
DOI: 10.18502/acta.v58i8.4592
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Characteristics of Mothers of Children With Cerebral Palsy

Abstract: The aim of the study was to determine the psychological characteristics of mothers of children with cerebral palsy. The study included a sample of 30 respondents. The sample consisted of mothers of children with cerebral palsy, chronologically aged 25 to 60. The research was conducted at the Centre for Children with Multiple Disabilities “Koraci Nade”. For the purpose of checking the set research aim, Symptom ChecklistSCL-90-R, consisting of a list of 90 particles (problems), was applied, and the task was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…S1). Table SIV (online supporting information) shows the number of articles in the databases before the application of the inclusion and exclusion criteria. It also describes the search syntax used in each of the databases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1). Table SIV (online supporting information) shows the number of articles in the databases before the application of the inclusion and exclusion criteria. It also describes the search syntax used in each of the databases.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the articles studied 1264 mothers and 105 fathers of children with CP, applying questionnaires and/or interviews about their children's condition and mental health status. Five studies involved control populations, four with 309 mothers of typically developing children and one with 171 mothers of children with other diseases. The article data can be found in summary form in Table SI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In another study significant psychopathology was found in 90% of mothers 14 Depression, anxiety, somatization and obsessivecompulsive disorders were the most detected problems. 14,15 It was found that depression and anxiety were higher in mothers of children with CP when compared with healthy children's mothers. 16,17 The depression levels of the mothers were positively correlated with the child's GMFCS score and negatively correlated with the WeeFIM score of child with CP.…”
Section: Discussionmentioning
confidence: 99%